Vulnerabilities for Marginalized Groups in the United States Forensic Anthropology Education System: Paths to Engagement and Belonging - Goliath, Jesse R.; Waxenbaum, Erin B.; Borgelt, Taylor S. (Humans, 2023)
Implicit and explicit barriers to building a culture of belonging persist in U.S. forensic anthropology. These barriers create and exacerbate vulnerabilities, especially among marginalized groups, that need to be addressed. The lack of diversity in U.S. forensic anthropology is well documented. At the same time, there has been a significant upswing in academic programs focusing on forensic anthropology at both the undergraduate and graduate levels. However, to be successful and promote retention, these programs must address the pervasive structural barriers that continue to impede diversity. Major impediments include the hierarchical structure, illusion of objectivity, racial and cis-gender-biased methodologies, and belonging uncertainty. At all levels, peer engagement and active, constructive mentorship may both semantically and structurally allow for a bridge between the past and the future. Pedagogy and professional practices in forensic anthropology must be modernized and restructured to promote learning environments that foster belonging and engagement.